Pro Poor Governance Dalam Pelayanan Publik - Tri Yumarni (Jurnal Administrasi Publik, 2005)
Poverty is a challenge and become responsibility of public administration, especially for the agenda of public management to give service delivery for citizens. Pro poor governance and eight measure for public service management solution is an alternative soultion for making service work for poor people. This framework based on three chain relations are between citizens and politicians, partnership between politicians and public service provider and partnership between public service provider and citizens through empowering voice of the poor.Kata kunci: Pro Poor Governance, Pelayanan Publik, MDGs